Valorization of Underutilized Biomass for Biorefinery and Food Applications: Exploring the Processing, Plant Material Composition, Bioactivity, and Fortified Bread Models - Fidelis, Marina (fi=Turun yliopisto|en=University of Turku|, 2024)
Strategies for a green bioeconomy transition are of worldwide importance and closely related to society's well-being. There is a growing demand for sustainable solutions that increase the efficient use and recycling of materials by utilizing side streams and reducing the dependence on non-renewable raw materials. The aim of this doctoral thesis was to address the value creation from underutilized plant biomass fractions, focusing on biorefinery and food systems through environmentally friendly and industrially feasible processes. Different underutilized biomass resources were investigated, and conifer-derived green needles were concluded to be the most promising in terms of chemical composition and bioactivities, which were further explored in bread models. Study I investigated common reed, reed canary grass, oil hemp, and fiber hemp as feedstock for a proposed biorefining process step, focusing on the fractionation and recovery of extractives and hemicelluloses as target components. The chemical characterization assessed the content of polyphenols, hemicelluloses, fatty acids, sugars, lipids, and proteins in the biomasses. Employing two-stage pressurized water extraction (90 °C/60 min + 160 °C/60 min) indeed improved the isolation of extractives and hemicelluloses, indicating overall higher yields of hemicelluloses, phenolics, and bioactivity compared to the single stage at 90 °C/60 min. In addition to introducing a biorefinery route approach, this study is the first detailed investigation into the composition of extractives from these biomass fractions. Consequently, it can serve as a foundation for future research. Study II explored a biorefinery-inspired possibility for a value-added utilization of industrially sorted Norway spruce green needle-rich logging residues. Pressurized liquid extraction optimization using response surface methodology identified optimal processing conditions – 120 °C for 10 min with water, and 125 °C for 68 min with ethanol/water – to maximize desired chemical composition (total phenolics and condensed tannins) and bioactivities (antioxidant and antibacterial properties). Under the optimized conditions, aqueous ethanol extraction resulted in a higher overall yield with increased antioxidant activities and bacterial inhibition compared to water. Study III examined a technological application of green needles and fine twigs (NT) from Norway spruce, silver fir and Japanese red pine by replacing water in bread at 0, 35, and 70% levels to assess effects on secondary metabolites, bioactivity, nutrition, and quality. NT-fortified bread showed good stability of compounds analyzed via high-performance liquid chromatography (HPLC-DAD) after 24 and 72 h, with a significant increase in several polyphenols after 72 h, correlating with over an 80% enhancement in antioxidant activity. A total of 115 compounds were identified, including flavonoids, phenolic acids, alkaloids, stilbenes, lignans, resin acids, and gibberellins. Overall, a 35% fortification was sufficient to improve functionality, extend shelf-life, and maintain nutritional and textural properties, while also enhancing overall acceptability and purchase intent. Among all formulations, bread fortified with pine NT at 35% levels exhibited the best overall balance of these factors, making it a promising option for further development as a bioactive, consumer-oriented product. The findings show the valorization potential of underutilized conifer NT as natural antioxidants and will help provide the industry with phytochemical compositional information. Also, this study emphasizes the broader applicability of these side streams by employing a green extraction technique (hydrodynamic cavitation) that yields valuable compounds, promotes sustainability, and supports the circular economy through a cost-effective process. Overall, this research offers essential insights into the effects of external factors and processing parameters on the properties of the studied biomass resources. It also highlights the potential of the underutilized fractions of plant species